Alfabetização científica e tecnológica com professores do ensino fundamental - Miranda, Marcos Cesar Rodrigues de (2017)
The Scientific and Technological Literacy (ACT) with Teachers of Elementary Education is a work that is being developed with the intention of guiding the teachers in their educative action with students, so that they have the importance of ACT in their daily life. The need for ACT insertion in the initial grades of schooling is justified by the change that results in each individual, who can understand the phenomena that surround him and thereby improve society. Knowing this, the objective of this research is the elaboration of a course targeting primary school teachers, with elements that can include ACT in teaching practice in elementary education, through which teachers can have contact with the main ideas about the Knowledge of practical activities in their daily classroom. Inserting ACT into teacher training and teaching practice, it reinforces the importance of reflective practice and continuing education. All the work will be developed using the Qualitative Approach as Research methodology and content analysis that as a method, becomes a set of communication analysis techniques that uses systematic procedures and objectives to describe the content of the messages. The research was based on a bibliographic review that sought in several articles the criteria chosen to compose the course, which were: theme, keyword and if possible demonstrate an application context. The instruments of data collection involved the analysis of articles for the elaboration of the modules, the production of questionnaires. This preliminary questionnaire aims to draw the profile of the target audience, reading and analyzing articles, discussion forums and questionnaires with objective and dissertative questions, and a proposal for the elaboration of a project at the end where the teacher uses his conceptions built during the course. We selected 3 articles per module, totaling 24 articles that will serve as a reference for study in the course. In an analysis of the results in the elaboration of the course, we can present some conclusions: In a course destined to the application in the distance mode one must take into account: the creation of a self instructional material so that it allows the student to have a proper learning pace, Assess the contents, allow self-evaluation, have the opportunity of immediate application of learning, develop autonomy of thought and action. The dynamics of the course must respect the reality of its target audience, its conceptions, schooling, professional profile, previous experiences related to the course and its reading habits. Construct a didactic material that allows an interaction with the participants and teacher and with their peers. Choose carefully the application platform so that it is a tool for facilitating the interaction between those involved. Clearly define the proposal and the evaluation criteria of the course, always aiming for a formative evaluation. We can conclude that the elaboration of a scientific and technological literacy course for elementary school teachers is extremely important to help them in this arduous task of building a society that is more just and concerned with the environment in which they live. Idea that the research can contribute to improve the education of the elementary school teacher and its practice.